Elevated C‐X‐C motif ligand 13 and B‐cell‐activating factor levels in neuromyelitis optica during remission. Issue 4 (10th March 2017) - Wang, Su; Yang, Tao; Wan, Jianglong; Zhang, Yongchao; Fan, Yongping
Abstract: Background: Discovery of specific antibodies against astrocytic water channel aquaporin‐4 (AQP4), which is produced by plasma cells, in the serum of neuromyelitis optica (NMO) confirmed the pathogenic role of B cells in NMO. C‐X‐C motif ligand 13 (CXCL13) and B‐cell‐activating factor (BAFF) are two crucial factors for antibody production. Relevant studies have focused on the acute phase of NMO. However, CXCL13 and BAFF levels during remission, remain to be elucidated. Objective: To evaluate serum levels of CXCL13 and BAFF in NMO and multiple sclerosis (MS) patients during remission and explore their correlation with immunosuppressive agents and clinical features in NMO. Methods: Serum CXCL13 and BAFF were measured by enzyme‐linked immunosorbent assay (ELISA) in NMO patients, MS patients, and controls. Results: Serum CXCL13 levels of NMO patients ( n  =   24) were significantly higher than those of controls ( n  =   22) ( p  =   .001), but CXCL13 levels of MS patients ( n  =   20) and controls ( n  =   22) did not differ significantly ( p  =   .279). Although the three groups showed no differences in serum BAFF levels, serum BAFF levels of NMO patients without immunosuppressive treatment ( n  =   8) were significantly elevated compared with those of NMO patients with immunosuppressive therapy ( n  =   16) ( p  =   .003) and controls ( n  =   22) ( p  =   .024). In NMO patients, CXCL13 levels were correlated with onset age ( p  =   .026) and duration to the last relapse ( p  =   .003). Conclusion: During remission, serum CXCL13 and BAFF levels have not decreased to normal in NMO patients, and B‐cell‐related autoimmune response persists. Immunosuppressive therapy decreased serum BAFF levels, but did not affect CXCL13 expression. Abstract : Serum levels of CXCL13 and BAFF aiming at remission of neuromyelitis optica were explored. Both of their levels were elevated. Immunosuppressive therapy could decrease BAFF expression, but did not affect CXCL13.